DAMPAK TATA KELOLA PERUSAHAAN TERHADAP KINERJA LEMBAGA PERBANKAN DI INDONESIA: Kasus Komposisi Dewan - Hersugondo, Hersugondo; Salsabilla, Talitha Sahda; Lesticya, Widya; Yuliastuti, Nur Rachmalina; Sidabutar, Maxsuel Herianto (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
Corporate governance is an important aspect in the company. The impact and implementation of corporate governance has become interesting for various companies because it substantially controls the management of institutions. This study analyzes the impact of elements of corporate governance (CG) which includes the composition of the board on the performance of banking institutions listed on the Indonesia Stock Exchange (IDX). The research population involved 25 banking institutions which are commercial banks in Indonesia. The data taken has a span of 4 years (2017, 2018, 2019, and 2020). Spearman correlation is used to identify the relationship between corporate governance and banking financial performance. The results of this study indicate that there is a positive relationship or correlation between the number of board personnel and the financial performance of commercial banks. The number of independent directors has a positive significant relationship with ROA, ROE and EPS, job duality has a positive significant relationship with ROA and EPS, and board meetings have no significant relationship with financial performance.